6ER-024 Aspirin compared to enoxaparin or rivaroxaban for the prevention of VTE following hip and knee replacement – a retrospective cohort study in ireland. (March 2019) - Ní Cheallaigh, S; Kehoe, E; O'Connell, C; Fleming, A; Sahm, LJ
Abstract : Background: The risk of venous VTE following major orthopaedic surgery is among the highest for all surgical specialties, and can result in significant morbidity and mortality. Guidelines for thromboprophylaxis following elective primary total hip or knee replacement (THR or TKR) in the Cappagh National Orthopaedic Hospital (CNOH) are based on American College of Chest Physicians (ACCP) guidance. The most recent change to local guidelines was the introduction of the extended aspirin regimen as standard thromboprophylaxis. Purpose: The aim of this study was to establish the effectiveness of this regimen by comparing VTE rates in patients receiving extended aspirin to those receiving inpatient enoxaparin or modified rivaroxaban regimens. Methods: This was a retrospective cohort study. Data were collected from the CNOH patient record software. All eligible patients who underwent primary TKR or THR between 1 January 2010 and 30 June 2016 were included (n=6, 548). Results: The overall VTE rate was 0.99%. The VTE rate in both the inpatient enoxaparin group (n=961) and extended aspirin group (n=3, 460) was 1.04%. The VTE rate in the modified rivaroxaban group (n=1, 212) was lower at 0.66%, but the difference was not statistically significant (p=0.154). A history of VTE was the only significant demographic risk factor for post-operative VTE (0.87% vs. 3.54%, p=0.0002). Conclusion: These findings confirm the effectiveness of our current standard thromboprophylaxis regimen. The results are generalisable to patients undergoing elective primary THR or TKR nationally and internationally. This study adds to the growing evidence supporting the use of aspirin thromboprophylaxis in the orthopaedic setting. References and/or acknowledgements: No conflict of interest.